The processing of Which interrogative sentences: A behavioral and ERP study - Grimaldi, Mirko; De Vincenzi, Marica; Lorusso, Paolo; Di Russo, Francesco; Di Matteo, Rosalia; Rizzi, Luigi; Guasti, Maria Teresa (Journal of neurolinguistics, 2023)
This study investigates the parsing of Italian Wh-questions of the Which-N type. The extraction site could be either the subject or the object noun phrase. The verb following the Which-noun was either a singular or a plural form, immediately disambiguating the Which-N argument role through verb agreement. Reading time on the verb and on the post-verbal noun phrase were significantly shorter for the subject Wh-question than for the object Wh-question. Multi-channel ERP data showed increased P600 amplitudes for the object questions in response to the critical word on the left temporal lobe in the superior temporal gyrus. These findings are in line with the Minimal Chain Principle (De Vincenzi, 1991a) and provide further evidence for the hypothesis that the amplitude and duration of the P600 involve multi-dimensional processes controlling operations such as prediction, retrieval, revising, and structure-building operations needed for assembly (and disassembly) of syntactic relations. •Which + N interrogatives involve extraction from either the subject or the object position.•Subject/object asymmetries are found in Which + N interrogatives.•Object Which + N involves higher reading times.•Which + N object sentences give rise to a P600 in the left superior temporal gyrus.•Further evidence on the idea that the P600 is a function of the assembly (and disassembly) of syntactic relations.